Digitalisasi Masyarakat: Menilik Kekuatan dan Kelemahan Dinamika Era Informasi Digital dan Masyarakat Informasi - AG. Eka Wenats Wuryantai (FISIP Universitas Atma Jaya Yogyakarta, 2004)
Some adagium which have been told by modern communications growth observer show that information become one of the vital element in society. Information become a fundamental requirement so that can be expressed as the lifeblood that sustains political, social and business decision. As a consequence, society has to expose themself with the growth and new media dynamics and global communications. The rotation in production, consumption and information distribution is faster experienced of and owned by global new society system supported by economic and extention power, global information system network and also contributed by digital technology. This Paper will explain some of alternative discourse to see the excess and weakness of information technologization process which finally instruct the society at digital era.